A Systematic Literature Review: SMEs Tax Compliance in National and Internatioanl Perspectives - Putri, Mareta; Fuadah, Luk Luk (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
Tax compliance is a strategic issue in the taxation systems of developing countries, including Indonesia, especially among Micro, Small, and Medium Enterprises (MSMEs) that contribute significantly to the Gross Domestic Product (GDP) but still show low levels of tax compliance. This study aims to conduct a Systematic Literature Review (SLR) of 30 national and international scientific articles discussing factors that influence MSME tax compliance. The results of the study indicate that Indonesian studies focus more on internal factors such as tax knowledge, awareness, socialisation, and fiscal services. In contrast, international studies emphasise structural and systemic factors such as the complexity of the tax system, compliance costs, trust in the government, and the effectiveness of digital and accounting systems. Quantitative approaches dominate the methods used, but there are variations in approaches in international studies. Cultural and economic differences influence policy orientation, with Indonesian studies promoting education and services, while international studies propose systemic reforms such as digitalisation and simplification of tax administration. These findings are expected to provide insights for policymakers to design more contextual and effective SME tax compliance strategies